The Community Empowerment in Kelapa Dua, Depok, through Hygiene Tempeh Production Training - Dionysius Subali; Anastasia Tatik Hartanti; Meda Canti (Institute for Research and Community Services, 2022)
Many people from various communities still do not understand the value of tempeh as a healthy food item. Therefore, to improve the public knowledge about the nutritional values of tempeh, Atma Jaya Catholic University of Indonesia chose the community of Bhayangkari women from Ranting, Kelapa Dua, Depok, as the target partners in the community service program. This community, which consisted of housewives of police officers, was considered the right target because they had the role of providing healthy food for their families. In addition to providing knowledge about the importance of consuming tempeh as healthy food, the team also trained the community to produce hygienic tempeh. The activities included three stages, i.e., preparation, implementation, and monitoring and evaluation. The program preparation involved the registration of the participants, the preparation of the seminar materials, and the procurement of materials and tools for the tempeh production. Next, the implementation stage consisted of education and training activities conducted via WhatsApp (WA) and Zoom meetings. Finally, the monitoring and evaluation stage was conducted via WA to assess the tempeh production process. Through this community service program, it is evident that all the participants could be trained on how to make hygienic tempeh easily. The guidelines to produce tempeh were also easy to understand and readily available for public use. Overall, the participants became more aware of the health benefits of tempeh.